Teshigawara/Karas 2004 Review - Phillips, Katie (Dance Books Ltd., Alton,Hampshire (UK), 2004)
PALABRAS CLAVE: Saburo Teshigawara, company Karas, Bones in Pages.
Dentro del apartado "Dance Now. 2004 Reviews".